The Mediating Role of Job Satisfaction in the Relationship between Transformational Leadership and Employee Creativity - Meilani, Ayla Nisha; Atika, Atika; Zainarti, Zainarti (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
This study aims to analyze the effect of transformational leadership on employee creativity and to examine the role of job satisfaction as an intervening variable among employees at a manufacturing company in Indonesia. The study uses a quantitative method with an explanatory design. The sample includes all 40 employees using a census technique. Data were collected through a five-point Likert scale questionnaire that measured respondents' perceptions of transformational leadership, job satisfaction, and employee creativity. Data analysis was performed using regression and path analysis to assess the direct and indirect effects between variables. The results showed that transformational leadership had a negative and significant effect on employee creativity. Meanwhile, transformational leadership did not have a significant effect on job satisfaction. Job satisfaction was found to have a positive and significant effect on employee creativity and acted as an intervening variable that explained the weakening of the direct effect of leadership on creativity when job satisfaction was taken into account. These findings indicate that employee creativity in procedural work environments is more sensitive to satisfying work experiences than to leadership encouragement alone. The implications of this study emphasize the importance of increasing job satisfaction through fair reward policies, role clarity, supportive feedback from superiors, and a work climate that is conducive and safe for the expression of ideas.